Childhood Cancers: Experience at a Tertiary Care Hospital - Asma Shabbir (Journal of Rawalpindi Medical College, 2011)
Background: To study the prevalence of childhood tumours in a paediatric unit of a tertiary hospital Patients and Methods: In this descriptive study 94 cases of childhood malignancies treated at a tertiary hospital were studied. Age, gender, type of malignancy and outcome were evaluated Results: Out of a total of 94 patients 69.1% were males and 30.9% were females. The most common malignancy was acute leukaemia (34%). Overall mortality was 48.94% Conclusion: The high mortality highlights the inadequacies in the treatment of childhood tumours